2016
DOI: 10.1128/aac.01008-16
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Spheroplasts as a Model for Visualizing Membrane Translocation of Antimicrobial Peptides

Abstract: Studies attempting to characterize the membrane translocation of antimicrobial and cell-penetrating peptides are frequently limited by the resolution of conventional light microscopy. This study shows that spheroplasts provide a valuable approach to overcome these limits. Spheroplasts produce less ambiguous images and allow for more systematic analyses of localization. Data collected with spheroplasts are consistent with studies using normal bacterial cells and imply that a particular peptide may not always fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Additionally, because we have not assessed the viability of spheroplast populations, one cannot distinguish between a peptide that is readily able to translocate across the cell membrane of a living cell versus a peptide that can only translocate across a dead or dying cell. Despite these differences, we have seen localization patterns in E. coli spheroplasts for many AMPs that are consistent with known mechanisms of action 15 , and our results for BF2 P11A with B. megaterium protoplasts presented here seem consistent with other observations for that peptide 13,27,28 . The membrane compositions of spheroplasts and protoplasts are also certainly more physiologically relevant than the typical mixtures used in other model systems, such as lipid vesicles.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, because we have not assessed the viability of spheroplast populations, one cannot distinguish between a peptide that is readily able to translocate across the cell membrane of a living cell versus a peptide that can only translocate across a dead or dying cell. Despite these differences, we have seen localization patterns in E. coli spheroplasts for many AMPs that are consistent with known mechanisms of action 15 , and our results for BF2 P11A with B. megaterium protoplasts presented here seem consistent with other observations for that peptide 13,27,28 . The membrane compositions of spheroplasts and protoplasts are also certainly more physiologically relevant than the typical mixtures used in other model systems, such as lipid vesicles.…”
Section: Discussionsupporting
confidence: 92%
“…By labeling the membrane of the bacteria, one can determine if a fluorescently labeled peptide localizes to the membrane or the intracellular space of a bacterial cell. However, this technique is limited by the small size and rod shape of bacteria, which can make imaging challenging due to the resolution limits of conventional light microscopes and the variable orientation of the bacteria on the slide 15 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, considering membrane translocation and DNA binding led to a more complete interpretation how proline mutants affect activity of BF2 [39]. Although AMPs are often characterized as primarily killing bacteria by either permeabilizing membranes or interacting with an intracellular component, several studies have proposed that at least some peptides may function through a combination of these different mechanisms [19, 23, 49]. Because of their well-characterized membrane and nucleic acid interactions, HDAPs may continue to provide a valuable model system for considering how different factors combine in AMP activity.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al . have reported that the antimicrobial peptide buforin II (BF2), and HipC (a cell-penetrating peptide) entered into the majority of spheroplasts, while BF2 with a P11A mutation and magainin localized with the membrane 40 . Nan et al .…”
Section: Discussionmentioning
confidence: 99%